Prescribing Trends of Fixed-Dose Combination Antibiotics Not Recommended by the WHO (FNRs) for ICU Patients in Six Major Areas of China During a Seven-Year Period - Zhou L; Zhao Y; Zhu J; Liu J; Liang G; Yang Y; Han G; Yu Z (Drug Design, Development and Therapy)
Liujun Zhou,1,* Yuhua Zhao,1,2,* Jianping Zhu,1 Jieqiong Liu,1 Gang Liang,1 Yi Yang,1 Gang Han,1 Zhenwei Yu1 1Department of Pharmacy, Sir Run Run Shaw Hospital, School of Medicine, Zhejiang University, Hangzhou, People’s Republic of China; 2Department of Pharmacy, Affiliated Xiaoshan Hospital, Hangzhou Normal University, Hangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Gang Han; Zhenwei Yu, Email 3199022@zju.edu.cn; yzw_srrsh@zju.edu.cnObjective: To evaluate the prescribing trends of fixed-dose combination antibiotics not recommended by the WHO (FNRs) for intensive care unit (ICU) patients in six major areas of China from 2013 to 2019.Methods: A descriptive analysis was conducted using the pharmacy prescription data. Prescription data for patients admitted to the ICU were extracted from the Hospital Prescription Analysis Cooperative Project. Trends in FNR use were analyzed over a seven-year period, and the trends were further analyzed at the specific drug and hospital levels.Results: A total of 15,596,620 prescriptions were eligible for analysis, and 1,492,793 patients were included. Among these patients, 91,515 (6.13%) received FNRs. The annual number of ICU patients who received FNR showed an increasing trend (P=0.007), but the percentage per year did not (P=0.764). The FNR use was usually higher in male patients than in female patients (P< 0.001). Patients aged > 60 years had the highest percentage of patients who received FNRs (P< 0.001). Among the eight FNRs identified in this study, cefoperazone/sulbactam was the most commonly used FNR in both patient numbers and prescribed hospitals, followed by piperacillin/sulbactam. The use of cefotaxime/sulbactam was less common but showed an increasing trend. There were significant differences among the regions.Conclusion: This study investigated the national landscape of FNR use among ICU patients. Attention should be given to the frequent use of FNRs in these patients. Data on the real-world effectiveness and safety of FNRs are urgently required.Keywords: antibiotic use, fixed-dose combination, irrational, prescription, cefoperazone, sulbactam